2021
DOI: 10.1007/s11764-021-01107-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting physical activity change in cancer survivors: an application of the Health Action Process Approach

Abstract: Purpose Previous research has not examined the utility of the Health Action Process Approach (HAPA) to predict physical activity (PA) change in cancer survivors. The aim of the study was to investigate the efficacy of a HAPA-based model in predicting temporal change in moderate-to-vigorous physical activity (MVPA) in cancer survivors. Methods Participants enrolled in the Wearable Activity Technology and Action Planning (WATAAP) trial completed validated qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…1 ). Two studies reported on different wearable device data about one patient population from Australia, 73 , 74 another 2 from the US in the late 2000s 150 , 151 and mid 2010s, 154 , 155 and another 2 from Canada 183 , 184 ; in total, 17 805 unique patients were reported across 195 unique datasets. There was a low risk of bias observed in the reported studies (>75%) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Two studies reported on different wearable device data about one patient population from Australia, 73 , 74 another 2 from the US in the late 2000s 150 , 151 and mid 2010s, 154 , 155 and another 2 from Canada 183 , 184 ; in total, 17 805 unique patients were reported across 195 unique datasets. There was a low risk of bias observed in the reported studies (>75%) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an additional note, the increasing interest in the Health Action Process Approach-related constructs such as social support may reveal an attempt from researchers to understand and document behavior maintenance processes. Indeed, past research has noted the importance of the Health Action Process Approach model for the understanding of PA behavior [142][143][144].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the 71 quantitative studies were conducted in the USA (n = 38, 53.5%) . The other studies were conducted in Canada [64][65][66][67][68][69][70][71], Australia [72][73][74][75][76][77][78][79], Germany [80][81][82], the Netherlands [83,84], the UK [85,86], Portugal [87], New Zealand [88], Sweden [89], Spain [90], Norway [91], the UK [85,92], Denmark [93], Taiwan [94,95], South Korea [96], Puerto Rico [38], and China [44]. The number of participants in these studies ranged from 23 [40] to 3000 [61].…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…15 out of 71 studies (i.e., 21.1%) had a cross-sectional study design and assessed changes in lifestyle behaviors following diagnosis and/or treatment retrospectively [26,31,32,62,67,73,76,78,79,83,[89][90][91][92]96]. 38 out of 71 studies (i.e., 53.5%) were intervention studies [27,28,[33][34][35][36][37][38][39][40][41][42][43][45][46][47][48]50,51,[53][54][55][56][57][58][59][60][68][69][70]74,75,77,81,82,…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation